SERVICE QUALITY IN DEMOCRATIC LEADERSHIP REVIEW - Martin Zebua (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to conduct an in-depth analysis of the type of democratic leadership and its impact on improving services to fishing pond customers. Through a qualitative research approach, the researcher identified and analysed various aspects of democratic leadership related to improving the customer service of fishing ponds. Data collection was conducted through in-depth interviews with managers and staff of fishing ponds that apply democratic leadership, as well as participatory observation to understand the dynamics of the work group. The results showed that strong democratic leadership plays an important role in influencing organisational culture, employee participation, and the quality of service to customers. The active participation of employees in decision-making, their involvement in designing and implementing policies, and the existence of a fair division of power all contribute to the improvement of responsive and quality services. In addition, this research highlights the importance of open and transparent communication between managers and employees, which allows for a strong sense of ownership, trust and collaboration. In the context of a fishing pond, democratic leadership creates a reliable work environment, where employees feel valued and encouraged to innovate, which ultimately impacts customer satisfaction.